Method for decomposing ammonium jarosite at low temperature and recovering resources respectively - HOU XIAOQIANG; TAN HONGBIN; WANG YU; MA XIAOLING; GUI HAIPING (2017)
The invention discloses a method for decomposing ammonium jarosite at low temperature and recovering resources respectively. The method comprises the steps as follows: pre-decomposing the ammonium jarosite in a low-temperature heat exchanger to obtain ferric sulfate powder and ammonia gas; adding a catalyst and a reducing agent to the ferric sulfate powder, mixing the materials evenly, and adding the mixed materials to a high-temperature heat exchanger for decomposing to obtain high-concentration sulfur oxide gas and iron oxide powder, and recovering valuable metal from the iron oxide powder. With adoption of the method, ammonia gas, sulfur oxide and the iron oxide powder can be recovered separately; compared with existing technical schemes, the method has the advantages that production cost can be saved, energy consumption is reduced, and efficiency is improved. 本发明公开了种铁矾渣低温分解及分别回收资源的方法，它是将铁矾渣在低温换热器中进行预分解，得到硫酸铁粉和氨气；再在硫酸铁粉中加入催化剂和还原剂，混合均匀后，加入高温换热器中分解得到高浓度氧化硫气体和氧化铁粉，从氧化铁粉中回收有价金属。本发明可单独回收氨气、氧化硫和氧化铁粉，同已有技术方案相比，本方